"Gender" views of Stanislav Orikhovsky (Ukrainian thinker of the first half of the 16th century) - V.D. Lytvynov; R. Mnozhynska (Українське Pелігієзнавство, 2008)
Gender is known to be a term used to define the sociocultural form of the existence of gender: man and woman act not as natural definitions but as sociocultural phenomena. If gender is determined on the basis of physical, organic and psychophysiological characteristics, then, unlike it, gender is derived from the social, cultural and historical features of human being. Human behavior in society and how it is perceived in it and defines gender as a social gender. Gender is thus one of the ways of social stratification of a society that, in combination with such socio-demographic factors as race, nationality, class, age, organizes the system of social hierarchy. Because gender is not a natural thing but a social construct, it implies self-awareness and self-determination. Gender has always been and remains a meaningful term. In the social sciences, "gender" has become more narrowly defined, denoting "social gender", that is, socially determined roles, identities and spheres of activity of men and women, which depend not on biological sexual differences, but on the social organization of society. Central to gender studies is the problem of social inequality between men and women.